2008
DOI: 10.1007/s12031-008-9045-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Phosphorylated cAMP Response Element Binding Protein (p-CREB) in Bladder Afferent Pathways in VIP−/− Mice with Cyclophosphamide (CYP)-Induced Cystitis

Abstract: The expression of phosphorylated cAMP response element binding protein (pCREB) in dorsal root ganglia (DRG) with and without CYP-induced cystitis (150 mg/kg, i.p; 48 hr) was determined in VIP −/− and wildtype (WT) mice. p-CREB-immunoreactivity (IR) was determined in bladder (Fastblue) afferent cells. Nerve growth factor (NGF) bladder content was determined by ELISAs. Basal expression of pCREB-IR in DRG of VIP −/− mice was (p ≤ 0.01) greater in L1, L2, L5-S1 DRG compared to WT mice. CYP treatment in WT mice inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 73 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…With respect to urinary bladder function, VIP −/− mice exhibit more pronounced urinary bladder hyperreflexia in response to CYP-induced cystitis compared to WT mice (Vizzard et al 2007). We have previously suggested that these differences may be due, in part, to differences in expression in urinary bladder inflammatory mediators under non-inflamed and inflamed conditions (Jensen et al 2008). The present studies demonstrate more robust upregulation of numerous inflammatory mediator genes in VIP −/− mice treated with CYP compared to WT mice treated with CYP.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…With respect to urinary bladder function, VIP −/− mice exhibit more pronounced urinary bladder hyperreflexia in response to CYP-induced cystitis compared to WT mice (Vizzard et al 2007). We have previously suggested that these differences may be due, in part, to differences in expression in urinary bladder inflammatory mediators under non-inflamed and inflamed conditions (Jensen et al 2008). The present studies demonstrate more robust upregulation of numerous inflammatory mediator genes in VIP −/− mice treated with CYP compared to WT mice treated with CYP.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have demonstrated that p-CREB expression in lumbosacral dorsal root ganglia was greater in VIP −/− mice under basal conditions and after bladder inflammation induced by cyclophosphamide (Jensen et al 2008). Urinary bladder from VIP −/− mice exhibit greater mass, increased thickness of detrusor smooth muscle, and increased neurotrophic factor (e.g., nerve growth factor) content compared to WT mice (Jensen et al 2008).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations